2010
DOI: 10.1103/physrevb.81.075308
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of quantum dot superradiance

Abstract: The possibility of realizing the superradiant regime of electromagnetic emission by the assembly of quantum dots is considered. The overall dynamical process is analyzed in detail. It is shown that there can occur several qualitatively different stages of evolution. The process starts with dipolar waves triggering the spontaneous radiation of individual dots. This corresponds to the fluctuation stage, when the dots are not yet noticeably correlated with each other. The second is the quantum stage, when the dot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 44 publications
1
34
0
3
Order By: Relevance
“…Inter-QW superradiant coupling can be induced and/or employed in multiple-QW periodic structures with Bragg resonances [128][129][130][131], quasi-periodic Fibonacci multiple-QW structures [132], and quasi-periodic double-period QW structures [133]. Moreover, theoretical studies of excitonic SR in quantum wires [134][135][136] and quantum dots [105][106][107][108][109][110][111] have provided additional predictions and incentives for experimental studies.…”
Section: A Excitonic Superradiance In Semiconductormentioning
confidence: 99%
See 1 more Smart Citation
“…Inter-QW superradiant coupling can be induced and/or employed in multiple-QW periodic structures with Bragg resonances [128][129][130][131], quasi-periodic Fibonacci multiple-QW structures [132], and quasi-periodic double-period QW structures [133]. Moreover, theoretical studies of excitonic SR in quantum wires [134][135][136] and quantum dots [105][106][107][108][109][110][111] have provided additional predictions and incentives for experimental studies.…”
Section: A Excitonic Superradiance In Semiconductormentioning
confidence: 99%
“…Zero-dimensional semiconductors, or artificial atoms, including quantum dots (QDs) and nanocrystals, provide another class of atomic-like systems in a solid-state environment for exploring cooperative emission [105][106][107][108][109][110][111][112]. Scheibner et al [113] investigated light emission properties of self-assembled CdSe/ZnSe QDs with individual dot sizes of 6-10 nm.…”
Section: Semiconductor Quantum Dots and Nanocrystalsmentioning
confidence: 99%
“…Dicke showed that, due to the mutual coupling between atoms through the electromagnetic field, the rate at which any one excited atom radiates is significantly influenced by the presence of all the other atoms. This phenomenon has been extensively discussed and experimentally observed for systems of free atoms [2][3][4][5], trapped ions [6], excitons in disordered π-conjugated polymers [7], artificial atoms represented by superconducting qubits coupled to a microwave cavity [8], Mössbauer nuclei [9], and an ensemble of individual quantum dots [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Eventualmente, essa propriedade permite ao experimentador induzir ou sintonizar interferências. Experimentos nessa direção tem sido bastante explorados por meio de materiais nanoestruturados como pontos quânticos [129][130][131], nanopartículas metálicas [132], e até mesmo com nanoestruturas mais complexas [133,134]. As interferências de natureza quântica também são vitais para a teoria de informação quântica, como discutem as Refs.…”
Section: Modelo De Dickeunclassified
“…Para uma cavidade com N átomos em seu estado excitado, este comportamento coletivo decorre a partir de um primeiro decaimento atômico. A radiação resultante induz os outros átomos a decaírem também, promovendo uma resposta positiva de grande amplitude [131], ou seja, um pulso com intensidade proporcional a N 2 [140,143]. Como consequência, o tempo de decaimento τ sr = τ sp /N de átomos no regime superradiante é N vezes menor que o tempo de decaimento por emissão espontânea individual τ sp .…”
Section: Modelo De Dickeunclassified